Hypoxia-induced Wnt5a-secreting fibroblasts promote colon cancer progression - Akikazu Harada; Yoshiaki Yasumizu; Takeshi Harada; Katsumi Fumoto; Akira Sato; Natsumi Maehara; Ryota Sada; Shinji Matsumoto; Takashi Nishina; Kiyoshi Takeda; Eiichi Morii; Hisako Kayama; et al. (Nature Communications)
Abstract Wnt5a, a representative Wnt ligand that activates the β-catenin-independent pathway, has been shown to promote tumorigenesis. However, it is unclear where Wnt5a is produced and how it affects colon cancer aggressiveness. In this study, we demonstrate that Wnt5a is expressed in fibroblasts near the luminal side of the tumor, and its depletion suppresses mouse colon cancer formation. To characterize the specific fibroblast subtype, a meta-analysis of human and mouse colon fibroblast single-cell RNA-seq data is performed. The results show that Wnt5a is expressed in hypoxia-induced inflammatory fibroblast (InfFib), accompanied by the activation of HIF2. Moreover, Wnt5a maintains InfFib through the suppression of angiogenesis mediated by soluble VEGF receptor1 (Flt1) secretion from endothelial cells, thereby inducing further hypoxia. InfFib also produces epiregulin, which promotes colon cancer growth. Here, we show that Wnt5a acts on endothelial cells, inducing a hypoxic environment that maintains InfFib, thereby contributing to colon cancer progression through InfFib.